Brushite mineralised Scots pine (Pinus sylvestris L.) sapwood – revealing mineral crystallization within a wood matrix by in situ XRD. Issue 9 (16th February 2023) - Garskaite, Edita; Balciunas, Giedrius; Drienovsky, Marian; Sokol, Denis; Sandberg, Dick; Bastos, Alexandre C.; Salak, Andrei N.
Abstract : Brushite mineral shows potential in wood reinforcement and development of hybrid calcium phosphate-based wood composites that could be particularly attractive in the construction sector as an environmentally friendly building material. Abstract : Dicalcium phosphate dihydrate (CaHPO4 ·2H2 O, DCPD, brushite) crystals were synthesised within Scots pine sapwood via a wet-chemistry route from aqueous solutions of Ca(CH3 COO)2 and NH4 H2 PO4 salts. SEM/EDS analysis was used to assess the saturation of the wood cell lumina and cell wall as well as morphological features and elemental composition of the co-precipitated mineral. Brushite mineral crystallization and crystallite growth within the wood matrix was studied by in situ XRD. The chemical composition of the mineral before and after the dissolution was evaluated using FTIR spectroscopy. The overall impact of brushite on the thermal behaviour of wood was studied by TGA/DSC and TGA/DTA/MS analysis under oxidative and pyrolytic conditions. Bending and compression strength perpendicular and parallel to the fibre directions as well as bending strengths in longitudinal and transverse directions of the mineralised wood were also evaluated. Results indicate the viability of the wet-chemistry processing route for wood reinforcement with crystalline calcium phosphate (CaP)-based minerals, and imply a potential in producing hybrid bio-based materials that could be attractive in the construction sector as an environmentally friendly building material.